Analisis Efektivitas Mesin Water Jet Loom Menggunakan Metode Overall Equipment Effectiveness (OEE) di Divisi Weaving PT X - Muhammad Izzul Haq; Tiaradia Ihsan (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
The Water Jet Loom (WJL) machines in PT X’s Weaving Division frequently experience operational disruptions, with a total downtime of 4,545 minutes, primarily in March and April 2025. This study evaluates WJL effectiveness using the Overall Equipment Effectiveness (OEE) method with a descriptive qualitative approach, focusing on availability, performance, and quality, based on downtime and production data from January to June 2025. Data collection techniques included observation, interviews, and analysis of downtime and production data. Data processing involved calculating availability, performance, and quality rates using OEE formulas. The results show an average OEE of 74.88%, below the global standard of 85%, with a performance rate of 80.99% and a quality rate of 93.92%. Fishbone analysis identified key causes: operator errors, suboptimal operational methods, unsupportive work environment, worn components, and delayed spare parts procurement. Therefore, improvements are needed in various factors contributing to reduced performance, as depicted in the fishbone diagram, to significantly enhance the OEE value. Keywords: Downtime, Machine Effectiveness, OEE, Water Jet Loom